Irrigation management transfer and the shaping of irrigation realities in Indonesia: from means to empower farmers to a tool to transfer rent seeking? - Suhardiman, Diana (2016)
Canal irrigation and the way it has been managed continue to be at the central stage of irrigation development debates. This article looks at Irrigation Management Transfer policy processes in the seven interconnected irrigation systems in Kulon Progo district, Yogyakarta province, Indonesia. It focuses on the government’s attempt to transfer funds for irrigation system operation and maintenance, so-called “stimulant funds,” from the irrigation agency to Federation of Water User Associations. Illustrating the transformation of the stimulant funds, from a policy measure to empower farmers to a tool to transfer rent-seeking practices, it urges the need to develop autonomous local organizations that are accountable to farmers and look beyond infrastructureoriented development as a basic foundation for irrigation policy reform.